Effect of copper on soluble proteins and enzymes in freshwater mussel Dreissena polymorpha: Abid A. Thaker and Ahmad S. Farhan - Thaker, Abid A. (The Iraqi Journal of Veterinary Medicine, 2010)
Dreissena polymorpha mussel were collected from Al-Kadesia lake - Haditha /Al- Anbar Governorate-Iraq. The animals were exposed to 1, 2 and 4 mg copper/l of water for eight days. The soft tissue was analyzed for the effect of copper on total protein components and activity of six enzymes (using colorimetric and /or electrophoretic methods). Copper was found to cause (a) Change in the intensity of some esterase patterns and increase of total protein by increasing the exposure time to copper (b) Increase in the activity of the enzymes, Aspartate amino transaminase (AST) and Alanine amino transaminase (ALT), and decrease in the activity of alkaline phosphatase (ALP) and acid phosphatase (ACP) . (c) Lactate dehydrogenase (LDH ) activity was decreased after exposure to the metal. These changes may be useful as an early indicator for water pollution with copper .